Asymmetric Impacts of Palm Oil Expansion and Industrial Downstreaming on Ecological Footprint: Evidence from Indonesia - Muhammad Ridwan Manulusi; Juan Gabriel Kaseger; Abd Malik Adlu; Estelita Monika Tungka; Sifra Jelita Sendow (Advances in Economics & Financial Studies, 2026)
Purpose: This study empirically investigates the asymmetric impacts of palm oil production, downstream industrialization, and trade openness on the ecological footprint. The primary objective is to determine whether environmental degradation responds differently to positive and negative macroeconomic shocks. Research Method: The research employs a nonlinear autoregressive distributed lag framework to analyze annual time-series data spanning 30 years. The analytical procedure involves descriptive statistics, unit root tests to confirm stationarity, nonlinear bounds testing for long-run cointegration, and short-run Granger causality tests. Results and Discussion: The empirical findings reveal a statistically significant asymmetric relationship. A positive shock in palm oil production exacerbates environmental degradation, while a negative shock is associated with measurable ecological recovery. Furthermore, downstream industrialization marginally reduces the ecological footprint in the long run, suggesting the potential for adopting circular economy practices. Conversely, trade openness slightly increases environmental pressures, indicating a global telecoupling effect in which international demand influences domestic industrialization and upstream expansion. Implications: To mitigate imported environmental burdens, producing nations must implement robust integrated policies. Strategic interventions, such as enforcing strict forest moratoriums, facilitating land swaps to degraded mineral soils, and accelerating sustainable certification for smallholders, are critical for achieving long-term ecological resilience. Originality: This research breaks new ground by employing a nonlinear framework to reveal asymmetric "ecological hysteresis," in which environmental recovery fails to keep pace with the degradation caused by palm oil expansion.